2012
DOI: 10.1038/ncomms1993
|View full text |Cite
|
Sign up to set email alerts
|

Multimode circuit optomechanics near the quantum limit

Abstract: The coupling of distinct systems underlies nearly all physical phenomena. A basic instance is that of interacting harmonic oscillators, giving rise to, for example, the phonon eigenmodes in a lattice. Of particular importance are the interactions in hybrid quantum systems, which can combine the benefits of each part in quantum technologies. Here we investigate a hybrid optomechanical system having three degrees of freedom, consisting of a microwave cavity and two micromechanical beams with closely spaced frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
253
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(261 citation statements)
references
References 38 publications
7
253
0
1
Order By: Relevance
“…For example state transfer as well as squeezing using double cavity OEMS has been studied [11]. Further cavities with many mechanical systems are enabling one to reach very near quantum limit [12].Lezama and coworkers [7] found that a simple three level lambda scheme cannot give rise to EIA. They considered optical transitions between the hyperfine states of atoms F → F ′ > F which showed the possibility of EIA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example state transfer as well as squeezing using double cavity OEMS has been studied [11]. Further cavities with many mechanical systems are enabling one to reach very near quantum limit [12].Lezama and coworkers [7] found that a simple three level lambda scheme cannot give rise to EIA. They considered optical transitions between the hyperfine states of atoms F → F ′ > F which showed the possibility of EIA.…”
mentioning
confidence: 99%
“…Our EIA is quite versatile as it would occur in metamaterials [15,16], plasmonics [8,17] or in systems with several mechanical elements [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1c). This cavity-mediated force has been shown to cause hybridization [22][23][24] and synchronization 25 of, and incoherent transfer of energy between 24 , mechanical modes. Cavity-mediated longrange interactions are also exhibited by the mechanical instability of an atomic gas within a transversely pumped optical cavity 26,27 .…”
mentioning
confidence: 99%
“…We also display that the mechanical squeezing is the quantum resource used in optimal quantum estimation on the frequency. In future, it is an interesting subject to utilize coherence of the multi-mode cavity optomechanics [74,75] to enhance the accuracy of quantum parameter estimation. a continuous observable W conditioned on the fixed parameter ϕ.…”
Section: Discussionmentioning
confidence: 99%